Production of Carotenoids from Oil Palm Empty Fruit Bunches: Selection of Extraction Methods - Mustofa Anshori; R Muhamad Jafar; Dianika Lestari; Made Tri Ari Penia Kresnowati (Journal of Engineering and Technological Sciences, 2022)
Public awareness of the importance of natural food colorants is increasing. Carotenoids is one of the coloring agents which widely used for food applications to give yellow, orange, or red color in food products. Natural carotenoids can be produced by extraction from various sources, such as carrots and palm oil, or from algae and fungi. Oil Palm Empty Fruit Bunches (OPEFB) as the biomass waste of palm oil industry may still contain carotenoid residue and thereby extraction of OPEFB constitutes the crucial step in carotenoid production. The effects of solvent used for the extraction as well as the size of different parts of OPEFB on the obtained carotenoid were evaluated. The experiments were performed by soxhlet extractor using n-hexane, ethanol, and isopropyl alcohol solvents at the boiling points of each solvent. The ratio of OPEFB to the solvent is 1:60 (w/v) with the variations of the OPEFB size. The results showed that the optimum carotene concentration was obtained from extraction using n-hexane to 1 cm OPEFB spikelet.